2011
DOI: 10.5301/ejo.2010.6101
|View full text |Cite
|
Sign up to set email alerts
|

Intravitreal Bevacizumab Associated with Grid Laser Photocoagulation in Macular Edema Secondary to Branch Retinal Vein Occlusion

Abstract: PurPose. To evaluate intravitreal bevacizumab (IVB) combined with grid laser photocoagulation in macular edema (ME) secondary to branch retinal vein occlusion (BRVO 1,3,6, and 12 months were 0.47±0.18 (p=0.031), 0.56±0.50 (p=0.031), 0.65±0.60 (p=0.008), and 0.66±0.65 (p=0.016), respectively. The mean CST values at 1,3,6, and 12 months were 295±60 μm (p=0.008), 333±114 μm (p=0.070), 339±80 μm (p=0.008), and 335±109 μm (p=0.008

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
16
0

Year Published

2012
2012
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 18 publications
(16 citation statements)
references
References 30 publications
0
16
0
Order By: Relevance
“…The mean number of injections was 8.9 in 0.3 mg ranibizumab group and 8.8 in 0.5 ranibizumab group after 12 months of followup time [40]. Salinas-Alamán et al [17] evaluated the effect of bevacizumab associated with grid laser in ME secondary to BRVO. In the study, IVB was administered at baseline followed by GLP 1 month after.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…The mean number of injections was 8.9 in 0.3 mg ranibizumab group and 8.8 in 0.5 ranibizumab group after 12 months of followup time [40]. Salinas-Alamán et al [17] evaluated the effect of bevacizumab associated with grid laser in ME secondary to BRVO. In the study, IVB was administered at baseline followed by GLP 1 month after.…”
Section: Discussionmentioning
confidence: 99%
“…Therefore, combined therapies may be a good option for the treatment of ME secondary to BRVO. The combination of IVT injection with GLP and the combination of intravitreal bevacizumab (IVB) injection with GLP have been proposed and have obtained positive outcomes [16, 17]. In the literature the efficacy of IVB monotherapy versus IVT combination with GLP in the treatment of diffuse diabetic macular edema was studied [18].…”
Section: Introductionmentioning
confidence: 99%
“…The possibility of reducing the required number of intravitreal injections of anti-VEGF agents in the treatment of ME has been pursued to decrease the treatment time and financial burden on patients as well as the risk of injectionrelated endophthalmitis [7][8][9][10][11]. Several small clinical trials reported that a combined intravitreal anti-VEGF injection and subsequent macular grid laser photocoagulation could reduce the required number of intravitreal anti-VEGF agent injections [8][9][10][11], but this was refuted by other studies [2,12,13].…”
Section: Introductionmentioning
confidence: 99%
“…Several small clinical trials reported that a combined intravitreal anti-VEGF injection and subsequent macular grid laser photocoagulation could reduce the required number of intravitreal anti-VEGF agent injections [8][9][10][11], but this was refuted by other studies [2,12,13].…”
Section: Introductionmentioning
confidence: 99%
“…Several smaller clinical trials described an injection reduction in India [10], Japan [11, 12], Italy [13, 14], and Spain [15], but these were refuted by larger multicenter trials [1-5, 9, 16-18]. However, we have observed 3 possible conditions that may make focal/grid laser treatment effective: (1) prompt focal/grid laser after intravitreal injection of anti-VEGF agents [9, 18], (2) long follow-up [9, 18], and (3) focal but not diffuse DME [19].…”
Section: Introductionmentioning
confidence: 99%